Pushing Higher or Lower? Divergent Parental Expectations and Compromises in Occupational Choice - Fischer-Browne, Melanie (Social inclusion, 2022)
Many adolescents in Germany are unable to realize their realistic occupational aspirations when they transition from school to vocational education and training (VET). However, little is known about the underlying circumstances and what the compromises look like when these adolescents come to take up a VET occupation. As parents perform an important socialization role, which is also influential in occupational orientation, this article examines the role of divergent parental expectations. Are parental expectations, which differ from adolescents’ realistic occupational aspirations, related to the probability that adolescents will take up different occupations than they originally aspired to? Are relatively higher or lower parental expectations associated with a corresponding direction of compromise formation? Are there differences between men and women in the relationship between divergent parental expectations and compromise formation? This empirical analysis is based on a sample of 1243 VET entrants from the starting cohort 4 of the National Educational Panel Study (NEPS). The compromise formation of the adolescents is measured by comparing their realistic occupational aspirations from ninth grade with their first VET occupation. Results from multinomial logistic regression models show that adolescents adjust their occupational choices to their parents’ divergent expectations. Women are more likely to make compromises that accommodate their parents’ higher expectations.